'Programmes of Real Cultural Significance': BBC2, the Sciences and the Arts in the Mid-1960s. Issue 3 (July 2017) - Boon, Tim
Abstract : The advent of BBC2 provides an ideal focus for the study of the place of science in culture. Existing historical work on the televisual representation of science and technology looks only at science programming. This article proposes that such an approach misses what the medium supplies to the account of its subject. As a corrective, this article compares the treatment of science with that of other intellectual and cultural subjects, taking the case of the four monthly programmes that occupied the channel's initial Saturday evening 8.45–9.30 slot, treating: science ( Horizon ), social science ( The Human Side ), literature ( Writers' World ) and music ( Workshop ). Considering questions of televisual technique and grammar, it uncovers a common genealogy for all but the social science programme in the style and conventions of the arts magazine, Monitor. This suggests that the comparative study of television programmes can help the historian address the difficult terrain of 'high' culture as it was negotiated in the fluid circumstances of the 1960s.